2017
DOI: 10.1093/pasj/psx071
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on the fine structure and dynamics of a solar jet. I. Energy build-up process around a satellite spot

Abstract: We report a solar jet phenomenon associated with successive flares on November 10th 2014. These explosive events were involved with the satellite spots' emergence around a δ-type sunspot in the decaying active region NOAA 12205. The data of this jet was provided by Solar Dynamics Observatory (SDO), X-Ray Telescope (XRT) aboard Hinode, Interface Region Imaging Spectrograph (IRIS) and Domeless Solar Telescope (DST) at Hida Observatory, Kyoto University. These plentiful data enabled us to present this series of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Roy [21] confirmed this finding and further proposed that significant magnetic flux change over a short time interval is also important for producing surges. Subsequent studies based on high-resolution observations revealed that evolving satellite sunspots are liable to launch recurrent jets through continuous collisions with the main sunspots [55,[88][89][90][91][92][93][94]. In quiet-Sun and coronal hole regions, small opposite-polarity magnetic elements can be recognized as the most conspicuous photospheric progenitor for many lower-energy, smallscale coronal jets.…”
Section: (B) Precursormentioning
confidence: 99%
“…Roy [21] confirmed this finding and further proposed that significant magnetic flux change over a short time interval is also important for producing surges. Subsequent studies based on high-resolution observations revealed that evolving satellite sunspots are liable to launch recurrent jets through continuous collisions with the main sunspots [55,[88][89][90][91][92][93][94]. In quiet-Sun and coronal hole regions, small opposite-polarity magnetic elements can be recognized as the most conspicuous photospheric progenitor for many lower-energy, smallscale coronal jets.…”
Section: (B) Precursormentioning
confidence: 99%
“…Roy [21] confirmed this finding and further proposed that significant magnetic flux change over a short time interval is also important for producing surges. Subsequent studies based on high resolution observations revealed that the appearance of evolving satellite sunspots are liable to launch recurrent jets through continuously collision with the main sunspots [55,[88][89][90][91][92][93][94]. In quiet-Sun and coronal hole regions, small opposite-polarity magnetic elements can be recognized as the most conspicuous photospheric progenitor for many lower-energy, small-scale coronal jets.…”
Section: (B) Precursormentioning
confidence: 99%
“…By combining modeling and observations, Cheung et al (2015) analyzed 4 jets originating from a pore embedded in the interior of a supergranule to obtain data-driven simulations that show that the emergence of magnetic field structures in the vicinity of a pore are compatible with recurrent jet formation. A recent case study, presented by Sakaue et al (2017Sakaue et al ( , 2018 showed that such flux emergence plays a significant role in producing one EUV AR jet.…”
Section: Introductionmentioning
confidence: 99%